First GB records of the invasive Asian shore crab, Hemigrapsus sanguineus from Glamorgan, Wales and Kent, England. (6th July 2015) - Seeley, Becky; Sewell, Jack; Clark, Paul F.
Abstract : The present contribution reports on the capture of two adult male specimens of the Asian/Japanese shore crab, Hemigrapsus sanguineus (de Haan, 1835) from Glamorgan, south Wales and Kent, southern England. These represent the first records of this species from mainland Great Britain.